Effect of Collagen Addition on Hydroxyapatite Synthesized via Sol-Gel for Bone Implant Materials - Rr Alvara Dahayunanda Agnetta; Muhammad Revansyah Ramadhani W; Sintha Soraya Santi; Nurul Widji Triana; Srie Muljani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Hydroxyapatite (HAp)–collagen composites have attracted considerable attention as biomimetic materials for bone implant applications due to their structural similarity to natural bone. This study aims to synthesize hydroxyapatite–collagen composites via the sol–gel method and to investigate the effect of collagen content and sintering time on the Ca/P ratio and microstructural characteristics. Collagen content ranged from 0.5 to 2.5 g, while sintering time ranged from 4 to 6 hours at 1100 °C. The synthesised materials were characterised using Atomic Absorption Spectroscopy (AAS), UV–Vis spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, and Scanning Electron Microscopy (SEM). The results indicate that increasing sintering time improves the Ca/P ratio toward the stoichiometric value of 1.67. Moderate collagen addition (1–1.5 g) produces the most stable Ca/P ratio, whereas excessive collagen reduces Ca²? availability due to interactions with functional groups. Collagen incorporation was confirmed by FTIR analysis, while SEM observations revealed reduced particle size to the submicron range and increased porosity, indicating improved microstructural properties. The optimal condition was 1.5 g collagen and 6 hours of sintering, yielding a Ca/P ratio close to 1.67 and favourable morphological characteristics. This study provides new insights into the synergistic effects of collagen incorporation and sintering time on the microstructural evolution of sol–gel-synthesised hydroxyapatite, highlighting its potential for biomimetic bone implant applications. Contribution to Sustainable Development Goals (SDGs):SDG 3: Biomedical Application (Bone implants)SDG 9 : Material Innovation